Réponses aux questions de recherche pour les chercheurs collaboratifs Partie II : Mesure de confinement (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Includes images
Keywords: Mass media; Prices; Livestock; Medical care; Education; Religion; Travel; Household Income; Water Rights; Access to Water; Trade Practices; Trade Regulations; Sociality; Senegal; Mobility; COVID-19 Pandemic